The effect of high temperatures on the survival rate of the red flour beetle Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) under laboratory conditions. - بودي توفيق (Latakia University Journal -Biological Sciences Series, 2025)
This research was conducted in the plant quarantine laboratory in the port of Latakia to study the effect of high temperatures on the survival rate of the red flour beetle T.castaneum under laboratory conditions Due to the high rate of beetle infestation among agricultural consignments imported and exported through the port of Latakia, the same applies to food stores as well. The results showed that the survival rate recorded its highest value at a temperature of 40°C and an exposure period of 15 minutes, amounting to 0.98. ±0.141, while 0.82±0.386 was recorded at an exposure period of 120 minutes at the same temperature. While a value of 0.78±0.416 was recorded at a temperature of 45°C and an exposure period of 15 minutes, and a value of 0.68±0.469 was recorded at a temperature of 120 minutes at the same temperature. At a temperature of 50°C, the survival rate recorded a value of 0.74±0.441 with an exposure period of 15 minutes, which decreased to 0.50±0.503 with an exposure period of 120 minutes, while the survival rate recorded a value of 0.30±0.461 at a temperature of 55°C and an exposure duration of 15 minutes, recording a value of 0 with an exposure duration of 120 minutes. 120 minutes at 60°C for different exposure times.